Determinan Kebijakan Hutang (Bukti Empiris Pada Perusahaan yang Terdaftar Di Bursa Efek Indonesia) - Linda, Linda; Lautania, Maya Febrianty; Arfandynata, Muhammad (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2017)
The purpose of this study is to examine the influence of asset structure, free cash flow (FCF), and investment opportunity set on debt policy in the LQ-45 company listed in the Indonesia Stock Exchange between 2011 and 2015.The data used in this study obtained from published companyfinancial statements. The sample was selected based on purposive sampling method e.g. 110 observations. The hypotheses were tested by using multiple linear regression analysis.The results of this study demonstrated that the asset structure, FCF, and investment opportunity set both partially and simultaneously determine the Debt to Equity Ratio. Partially, this study found that the asset structure and FCF has a negative influence on debt to equity ratio, while the investment opportunity set has a positive influence on debt to equity ratio. based on these results, the good investment opportunity set have a strong relationship on the level of debt risk.